The state of development of artistic and creative abilities of students in the classroom of applied decorative and applied art in modern educational practice - Khaytmetov Dilshodjon Turayevich (Genius Publishing Group, 2023)
The system of art education and upbringing can be understood only as an immanent reproduction of the needs of a Social Organism from a specific model of society. Only through the mechanism of artistic education can the purposeful development of creative abilities be carried out by rethinking the "I" of humanity (Hegel), the translation of external cultural structures (social norms, attitudes, tastes, needs) into internal stimuli of personality behavior, assuming the unity of aesthetic beliefs of the individual. his intuitive orientations and self-expression in all forms of artistic activity
Keywords: art; crafts; research; abilities